1992
DOI: 10.1113/jphysiol.1992.sp019380
|View full text |Cite
|
Sign up to set email alerts
|

Calcium currents at motor nerve endings: absence of effects of adenosine receptor agonists in the frog.

Abstract: SUMMARY1. The effects of adenosine (50 fIM) and 2-chloroadenosine (1-25 /M) were studied on Ca2+ currents in frog motor nerve endings.2. Ca2+ currents associated with the synchronous, neurally evoked release of acetylcholine (ACh) were measured using either perineural or patch recording methods. Tetraethylammonium and/or 3,4-diaminopyridine were employed to block K+ currents.3. Ca2+ currents were depressed by wo-conotoxin (1-5-2-5 gM), Cd21 (100 fM-2 mM), Co2+ (500 /M-5 mM) or by a reduction of the extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 53 publications
2
91
1
Order By: Relevance
“…A neuromodulatory action of CCPA via a decrease in Ca 2 þ influx was also observed at the mammalian neuromuscular junction when nerve terminals were stimulated electrically (Hamilton & Smith, 1991). In contrast, at frog neuromuscular junctions, this mechanism was not found to be associated with the inhibitory action of AD (Silinsky & Solsona, 1992;Redman & Silinsky, 1994;Robitaille et al, 1999), suggesting that, in this species, as in other tissues, the nucleoside inhibits tonic secretion by modulating the release machinery downstream of Ca 2 þ influx (Prince & Stevens, 1992;Scanziani et al, 1992;Scholz & Miller, 1992;Capogna et al, 1996;Dittman & Regehr, 1996; for a review see Wu & Saggau, 1997). In order to investigate which of the VDCCs was involved in the presynaptic effect of CCPA, we studied the different blocking effects of specific VDCC blockers and CCPA on mepp frequency.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A neuromodulatory action of CCPA via a decrease in Ca 2 þ influx was also observed at the mammalian neuromuscular junction when nerve terminals were stimulated electrically (Hamilton & Smith, 1991). In contrast, at frog neuromuscular junctions, this mechanism was not found to be associated with the inhibitory action of AD (Silinsky & Solsona, 1992;Redman & Silinsky, 1994;Robitaille et al, 1999), suggesting that, in this species, as in other tissues, the nucleoside inhibits tonic secretion by modulating the release machinery downstream of Ca 2 þ influx (Prince & Stevens, 1992;Scanziani et al, 1992;Scholz & Miller, 1992;Capogna et al, 1996;Dittman & Regehr, 1996; for a review see Wu & Saggau, 1997). In order to investigate which of the VDCCs was involved in the presynaptic effect of CCPA, we studied the different blocking effects of specific VDCC blockers and CCPA on mepp frequency.…”
Section: Discussionmentioning
confidence: 95%
“…At the frog neuromuscular junction, it has been shown that the inhibitory effect of AD upon evoked and spontaneous neurotransmitter release is not related to a reduction in calcium influx through the N-type voltage-dependent calcium channels (VDCCs), suggesting that AD exerts its action at a site distal to the locus of Ca 2 þ entry (Silinsky, 1984;Silinsky & Solsona, 1992;Redman & Silinsky, 1994). On the other hand, Hamilton & Smith (1991) showed that, at rat neuromuscular synapses, AD inhibits the motor nerve terminal Ca 2 þ current in response to nerve stimulation, but the mechanism(s) by which AD induces presynaptic inhibition of spontaneous neurotransmitter release remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plausible mechanisms for the prejunctional inhibitory e ect of adenosine analogues on mepp frequency which have been proposed are: a decrease in the ability of Ca 2+ to promote the exocytosis process (e.g. Silinsky, 1984Silinsky, , 1986Silinsky & Solsona, 1992) or a decrease in Ca 2+ entry via Ca 2+ channels (Hamilton & Smith, 1991). However, the latter explanation appears to be less likely in these present experiments because we have restricted this study to spontaneous ACh release which, in the absence of nerve terminal depolarization, is little in¯uenced by extracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Previous results suggest that adenosine inhibits ACh secretion in frog without reducing Ca2+ influx through voltagedependent Ca2' channels (Silinsky, 1981(Silinsky, , 1984Silinsky & Solsona, 1992;Hunt & Silinsky, 1993). We have now investigated the possibility that adenosine reduces the amount of cytoplasmic Ca2+ available to trigger secretion by increasing the rate at which Ca2+ is removed from the cytoplasm adjacent to the active zone.…”
Section: Introductionmentioning
confidence: 99%